Thermal, Structural, and Crystallization Properties of New Tantalum Alkali-Germanate Glasses - Pietro, Gabriele Matinatti de; Pereira, Camila; Goncalves, Rogeria Rocha; Ribeiro, Sidney J. L. [UNESP]; Freschi, Carolina Dakuzaku; Cassanjes, Fabia Castro; Poirier, Gael (Wiley-Blackwell, 2015)
In this work, new glass compositions were prepared in the ternary system GeO2-K2O-Ta2O5. Potassium oxide was added to reach the complete melt of the starting mixture and two composition series were investigated: the first one with a constant K2O molar content of 10% in the ternary system (90-x)GeO2-10K(2)O-xTa(2)O(5) and the second one with the same molar content of K2O and Ta2O5 in the ternary system (100-2x)GeO2-xK(2)O-xTa(2)O(5). Homogeneous and transparent glasses could be obtained between x=0 and 20. X-ray diffraction analyzes of samples with x=25 identified orthorhombic Ta2O5 in the first series and an isostructure of K3.8Ge3Nb5O20.4 in the second series where it is assumed that Ta5+ ions are inserted in the Nb5+ sites. As one of our goal with these materials is related with the preparation of glass-ceramics containing Ta2O5 nanocrystals, the first series has been selected for further characterizations. An increase in glass-transition temperatures with increasing Ta2O5 content as well as an increase of the thermal stability from x=0 to 10 has been identified by differential scanning calorimetry. For higher contents, crystallization events were identified. Fourier transform infrared and Raman spectroscopic characterizations allowed to point out the intermediary behavior of Ta2O5 in the vitreous network where TaO6 octahedra are inserted inside the germanate network with TaO6 clusters identified at higher Ta2O5 contents. Heat-treated samples with high tantalum contents (x=15 and 20) exhibit preferential precipitation of orthorhombic Ta2O5 with nanometric size, suggesting the possibility of obtaining transparent glass-ceramics for optical applications.